The problem of salvation according to Josiah Royce - Alaa Al Deen, Ghassan; Abboud, Janet (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research deals with the new proposition presented by the American philosopher Josiah Royce to the problem of salvation, in which he tries to discuss the heated debate between the religious thinkers who limited the path of salvation to what is divine and divisive, and between the moral thinkers who viewed salvation and treated it as a human act above anything else. This is in order to put an end to such a supposed argument between them by means of revealing the harmonious dimension between religion and ethics which was absent from the minds of plenty of their followers.